Pemanfaatan karbon aktif dari sabut kelapa sebagai elektroda superkapasitor - Farly Reynol Tumimomor; Septiany Christin Palilingan (Jurnal Kimia Fullerene, 2018)
In this study, coconut fiber based activated carbon has been used for fabrication of supercapacitors. Iodine absorption test is performed to measured absorption level porous activated carbon sample size is relatively small (microporous). Characteristics of the activated carbon material covering the surface morphology and structure were tested using SEM and XRD. Electrode materials with composition (Activated charcoal: PVDF = 9: 1 (w / w)), the current collector and separator has been assembled to be tested its performance as an electrical charge storage device. The test results by cyclic voltammetry method was to look at the performance supercapacitor devices at once to obtain the value of the capacitance curve obtained voltammograms. Based on the results of the calculation of the capacitance, the highest capacitance values ​​obtained in the supercapacitor with activated carbon electrodes in coconut fiber steam 50 mL / bar with a capacitance value is 50.73 F / g.